Effect of Pandanus tectorius extract as food additive on oxidative stress, immune status, and disease resistance in Cyprinus carpio. Issue 120 (January 2022) - Cheng, Chi; Park, Se Chang; Giri, Sib Sankar
Abstract: The present study investigated the effect of Pandanus tectorius (PT) extract on Cyprinus carpio growth, antioxidant capacity, immunological and oxidative stress, immune-related gene expression, and resistance against pathogen challenge. Fish (average weight: 12.18 ± 0.32 g) were fed with diets containing various concentration (g kg −1 ) of PT extract: 0 g (basal diet), 5 g [PT5], 10 g [PT10], 20 g [PT20], and 30 g [PT30] for 8 weeks. Our results revealed an increase ( p  < 0.05) in the final weight gain only in the PT20 (63.12 ± 1.4 g) group. Activity of liver antioxidant parameters such as catalase (CAT) (27.67 ± 1.12 U mg protein −1 ), superoxide dismutase (SOD) (13.17 ± 0.428 U mg protein −1 ), and glutathione peroxidase (GPx) (47.14 ± 1.47 U mg protein −1 ) was highest in the PT20 group. Among the serum immunological parameters examined, lysozyme (37.45 ± 0.67 U mL −1 ), alternative complement pathway (133.22 ± 1.92 U mL −1 ), and phagocytic activities (25.68 ± 0.93%) were high ( p  < 0.05) in PT20, whereas there was no significant effect on serum immunoglobulin or total protein levels, compared to the control. Serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), and malondialdehyde (MDA) levels were found to be lower ( p  < 0.05) in the PT20 and PT30 groups than those in the control. However, myeloperoxidase (MPO) levels were significantly higher ( p  < 0.05) in the PT20 and PT30 groups. Gene expression analysis revealed that mRNA expressions of antioxidant genes ( SOD, CAT, nuclear factor erythroid 2-related factor 2) and anti-inflammatory cytokine ( IL-10 ) genes were significantly upregulated in the PT10 – PT30 groups, except for the SOD gene in PT10. Conversely, the signalling molecule NF-κBp65 was downregulated in PT20 and PT30. Expression of Toll-like receptor 22 ( TLR22 ) and hepcidin was significantly upregulated in PT20 and PT30, respectively. Fish in the PT20 group exhibited highest relative post-challenge survival (70.37%) against Aeromonas hydrophila challenge. The results of the present study suggest that dietary supplementation of P. tectorius extract at 20 g kg −1 can significantly improve weight gain, serum antioxidant parameters, strengthen immunity, and increase the disease resistance of C. carpio . Therefore, P. tectorius extract could be exploited for its use as a food additive in aquaculture. Highlights: Pandanus tectorius extract improved antioxidant status of Cyprinus carpio. It also improved the immune status and disease resistance in C. carpio. It altered the expression of antioxidant- and inflammation-related genes. Fish fed 20 g kg −1   P. tectorius extract showed highest disease resistance capacity.